Individual differences in the processing of referential dependencies: Evidence from event-related potentials. (23rd April 2018) - Fiorentino, Robert; Covey, Lauren; Gabriele, Alison
Highlights: Examined referential ambiguity and referential failure using ERP. Two different responder types emerged in the processing of referential ambiguity. P600 elicited by referential failure in absence of an acceptability judgment task. Abstract: The present study examines the processing of referential ambiguity and referential failure using event-related potentials (ERPs). Participants read sentences with pronouns ( he, she ) which contained either one, two, or no potential gender-matching antecedents. Participants also took tests of working memory (Count Span/Reading Span) and attentional control (Number Stroop). In contexts of referential ambiguity with two potential gender-matching antecedents, two different responder types emerged, with some participants yielding a sustained negativity (Nref) and others a sustained positivity. For individuals who elicited Nref, the size of the effect was related to working memory such that higher Count Span scores were related to a larger Nref. For individuals who elicited a positivity, the effect was marginally related to attentional control such that better performance on the Stroop was related to a less positive, or increasingly negative-going ERP effect. Contexts of referential failure, with no gender-matching antecedents, yielded P600 for all participants, suggesting that participants may treat the failure of the pronoun to agree in gender with the antecedents as a violation despite the absence of an explicit acceptability judgment task.